The Effect Of Promotion And Location On The Purchase Decision Of Honda New Vario 150 CBS Motorcycle At PT Tunas Dwipa Matra Melawi Regency - Ricky Ramadhan; Sukardi Sukardi (UNIVED Press, 2025)
This study aims to identify the effect of promotion and location on the purchase decision of Honda New Vario 150 CBS motorcycle at PT Tunas Dwipa Matra, Melawi Regency. This study adopts associative approach with purposive sampling method. A total of 100 respondents who had bought a Honda New Vario 150 CBS motorcycle at PT Tunas Dwipa Matra became part of this research sample. Data analysis was conducted using multiple linear regression through SPSS software version 25. The testing process in this study includes validity, reliability, normality, linearity, and multicollinearity. Hypothesis testing is done by using simultaneous test (F test) and Partial Test (t test). Based on the results of hypothesis testing, both simultaneously (F test) and partially (T test), it can be concluded that promotion and location together have a significant positive impact on purchasing decisions. In addition, both also show an independently positive and significant influence on the purchase decision.